Influenza A virus circulation in backyard animals in the Pacific coast of Guatemala, 2013–2014. (25th May 2022) - Müller‐Theissen, Maria L.; Azziz‐Baumgartner, Eduardo; Ortiz, Lucia; Szablewski, Christine M.; Alvarez, Danilo; Gonzalez‐Reiche, Ana S.; Jara, Jorge; Davis, C. Todd; Cordon‐Rosales, Celia
Abstract: Due to their documented epidemiological relevance as hosts for influenza A viruses (IAV), humans, poultry and pigs in backyard production systems (BPS) within wetlands could be key to the emergence of novel IAV variants able to transmit between humans or animals. To better understand the circulation of IAV at the human–animal interface of BPS within wetlands, we studied IAV in backyard duck flocks and pig herds in the Pacific Coast of Guatemala. From April 2013 to October 2014, we estimated the monthly IAV per cent seropositive and viral positive flocks and herds in two resource‐limited communities. We detected antibodies in sera against the IAV nucleoprotein through ELISA. We also detected IAV viral RNA in respiratory (ducks and pigs) and cloacal (ducks) swabs through rRT‐PCR directed at the matrix gene. We attempted viral isolation in eggs or MDCK cells followed by sequencing from swabs positive for IAV. During our study period, IAV seropositivity in duck flocks was 38%, and viral positivity was 23% ( n = 86 BPS sampled). IAV seropositivity in pig herds was 42%, and viral positivity was 20% ( n = 90 BPS sampled). Both flocks and herds had detectable antibodies against IAV mostly year‐round, and IAV was detected in several months. We isolated an H3N2 virus from one pig sampled at the end of 2013. Standard nucleotide BLAST searches indicate that the isolated virus was similar to seasonal viruses circulating in humans, suggesting human‐to‐pig transmission. Our data show concurrent circulation of IAV in multiple species of poultry and pigs that were commingled in rudimentary conditions in proximity to humans, but no significant risk factors could be identified.